2018
DOI: 10.1111/jfb.13663
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic rates and the energetic cost of external tag attachment in juvenile blacktip sharks Carcharhinus limbatus

Abstract: This study reports on the metabolic rate of the blacktip shark Carcharhinus limbatus and the energetic costs of external tag attachment. Metabolic rates, swimming speed and tail‐beat (BT) frequency were measured in a static respirometer with untagged animals and animals equipped with a small data logger. Tagged sharks showed significantly higher routine oxygen consumption and lower swimming speeds than untagged animals, indicating that tagging significantly affected the swimming efficiency and energetic requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…Lateralisation exhibits high and context-dependent variability 40 but has not been widely studied in sharks 41 . Alternatively, for a trait like ODBA for which sources of measurement error in sharks are understood, observed variability is likely due to accelerometers being too large 42 , dorsal fins of neonates not being rigid enough for attachment 43 , and the brevity of monitoring that precluded us from accounting for circadian activity rhythms. Among haematological traits, variability in blood pH, for instance, can result because arterial blood cannot be selectively sampled in elasmobranch fishes using caudal puncture 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lateralisation exhibits high and context-dependent variability 40 but has not been widely studied in sharks 41 . Alternatively, for a trait like ODBA for which sources of measurement error in sharks are understood, observed variability is likely due to accelerometers being too large 42 , dorsal fins of neonates not being rigid enough for attachment 43 , and the brevity of monitoring that precluded us from accounting for circadian activity rhythms. Among haematological traits, variability in blood pH, for instance, can result because arterial blood cannot be selectively sampled in elasmobranch fishes using caudal puncture 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the present study recommends at least a doubling of replicate groups that should be tested in a simple 2 × 2 experimental design, which, in this case, would involve collecting and testing half of the annual neonate population around Moorea, which is not practically feasible. Moving forward, reducing measurement error for traits like activity level and metabolic rate will be paramount in future studies on active shark species and will possibly involve the development and validation of custom equipment, including respirometry systems 49,50 and data-loggers 42,51 . Controlling for inter-individual variation is likely to be the more challenging endeavour, but this could be addressed by increasing the difference in temperature and pCO 2 conditions between treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, most existing guidelines for tag impact do not advise on appropriate tag size, placement positions or configurations (Rosen et al, ) and many are relatively naïve to the impacts of drag that are most relevant to marine and aerial applications (see Appendix for an overview). We anticipate that the reporting of drag values in future publications may help improve future guidelines and address recent requests in the literature for improved reporting of impacts (Bodey et al, ; Lameris & Kleyheeg, ) and better assessment of tag‐induced effects (such as drag) prior to deployment in the field (Lear et al, ). While we do not expect our findings to be taken up as formal guidelines, nor the use of CFD to be made compulsory, we hope that this work, and specifically our step‐by‐step guide (Appendix ), will aid the biologging community in achieving this.…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, for projects involving tags on aerial and aquatic animals, the focus on weight by most existing tag guidelines -for example the 3% or 5% rule (Casper, 2009) -ignores aero/hydrodynamic impacts (most notably drag) which are key in modulating energy expenditure and behaviour during swimming (Cornick, Inglis, Willis, & Horning, 2006;Culik & Wilson, 1991;Rosen, Gerlinsky, & Trites, 2017;van der Hoop et al, 2018) and flight (Bowlin et al, 2010;Pennycuick, Fast, Ballerstädt, & Rattenborg, 2012; but see Tomotani, Bil, Jeugd, Pieters, & Muijres, 2019). This may lead to biased data which are not representative of freely moving animals (Barron, Brawn, & Weatherhead, 2010;Lear, Gleiss, & Whitney, 2018;Ropert-Coudert et al, 2000), as well as raising important ethical concerns for the animal being tagged (Wilson & McMahon, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…spawning, migration, reproduction) for pelagic sharks released from fishing gear but carrying PSATs was probably not detrimental to their health (Jepsen, Thorstad, Havn & Lucas, 2015;Lynch, Marcek, Marshall, Bushnell & Bernal, 2017;Musyl, Domeier et al, 2011). Should PSATs or other tags remain attached for prolonged periods, the possibility exists that extra drag and energetic costs could affect long-term fitness and health outcomes (Bouyoucos, Montgomery, Brownscombe, Cooke & Suski, 2017;Bouyoucos, Suski, Mandelman & Brooks, 2017;Lear, Gleiss & Whitney, 2018), but there was no evidence of increased mortality with time-to-event and the bulk of F r occurred within 40 days of release. Finally, Guida (2016) and Wosnick et al (2019) demonstrated population-level effects in small rays and sharks exposed to fishing, but it remains unresolved whether these findings can be extrapolated to other pelagic elasmobranchs.…”
Section: Mortality Comparisons Of Pelagic Sharksmentioning
confidence: 99%